Soziologie - Sociology in the German-Speaking World Special Issue Soziologische Revue 2020 - Hollstein, Betina; Greshoff, Rainer; Schimank, Uwe; Weiß, Anja (De Gruyter, 2021)
This book provides the first systematic overview of German sociology today. Thirty-four chapters review current trends, relate them to international discussions and discuss perspectives for future research. The contributions span the whole range of sociological research topics, from social inequality to the sociology of body and space, addressing pressing questions in sociological theory and innovative research methods.